Factors influencing Value Added Tax Compliance in the construction industry in Thika Sub County-Kiambu County: moderating effect of technology - Yego, J. J. (Strathmore University, 2024)
Taxation constitutes a significant revenue stream for governments in both developing and developed nations. Tax compliance is influenced by several factors, and this study sought to investigate the factors that influence VAT compliance in the construction industry. The objective of this research was to investigate the factors that influence Value Added Tax compliance within construction companies and contractors operating in Kiambu County, with a particular emphasis on Thika Sub-County. This research was grounded in both the economic deterrence theory and the ability to pay theory. The moderating variable under consideration was technology, specifically the degree of automation within the firm. The positivism research philosophy guided the research which employed survey research design. The study sample was the 60 actively registered contractors and construction companies. Descriptive statistical analysis included mean and standard deviation while Inferential statistical analysis included Correlation analysis(r) and multiple regression which helped in establishing the relationship between variables. The research findings indicated that all the five examined factors i.e tax knowledge, compliance costs, tax enforcement measures, taxpayer attitudes and perceptions and technology as a moderating factors had an impact of value added tax compliance. The Cost of compliance and enforcement measures had a negative but significant effect while Tax knowledge, and attitude and perception together with use of technology as a moderating factor had a positive significant effect on the VAT compliance in the construction sector. The research recommended that the government should look at ways of reducing compliance costs by looking at other affordable alternatives to ETR machines, and to upload more relevant and useful educational resources online. This research suggests that further study be carried out to understand the uniqueness of the construction industry as far as tax enforcement measures are concerned, as the findings of this study were not consistent to earlier studies done on the same. Key Words: Tax Compliance, Compliance Cost, Enforcement measures, Tax Compliance, Tax non-compliance, Taxpayer Services, Taxation Knowledge.
Full - text thesis